CHALLENGES AND ALTERNATIVE OF CREATIVITY DEVELOPMENT IN HIGHER EDUCATION - Yunus, Muhammad (Journal of Humanity, 2015)
Creativity is the human ability to think, modify, discover and create something. Creativity in the scientific world and the general public is common term. In reality, creativity and human life are two different things, but inseparable, thus affecting and closely correlated. Life and civilization will stagnate and vacuum without creativity. Creativity always presents and appears in the rhythm of space and time as the level of thinking and the human needs. Problems faced by higher education in Indonesia today is the low creativity of both students and lecturers. Those are caused by: (1) creativity is not taught in higher education, (2) the creativity of students is less supported by parents, (3) the leader of higher education considers creativity as a means of damaging the system or existing products, and (4) the routines of lectures and students. In order to develop creativity in higher education, then the leader and lecturers should eliminate bad habits in destroying the creativity of subordinates and students, parents should continue the natural talent of the child, select the childâs social environment, minimizeÂ  punishment, and do not curb excessivelyÂ  child to âdoâ something. Ways that can be taken to intensify creativity in higher education including by the use of creative techniques based practical such as: brainstorming, incubator method, and the method of mapping the mind